Spanish socialism: on the road to Marbella - Petras, James F. (Contemporary crises, 1990)
This essay analyzes the underlying social and economic forces that explain the gap between the Spanish Socialist Party's working class base and its pro-business supply-side economic policies. The essay examines the ascendancy of a new professional class linked to financial capital and European multi-national capital that challenges the industrial policies of the Franco right. From an analysis of incomes policy, economic deregulation and state allocation, the study concludes that the Socialists have displaced the traditional Right as the principal representatives of corporate capital — they have become the New Right.